(untitled) (Global Journal of Human-Social Science, 2023)
In this study we were concerned with analyzing the life narratives of adolescent girls-mothers and fathers based on their stories their voices and the terms in which they narrate their experiences We wanted to explore themes that are not usually addressed in studies on teenage pregnancy and that require attention to the actors voice and listening to it It should be noted that we were based on an approach inspired by grounded theory We will say that pregnancy presents itself as a stage of discovery for girl-mothers There are sorrows doubts uncertainties that will progressively cease to exist in order to be able to build their own pregnancy Temporarily we are facing a phase outlined with the appearance of changes whether physical or psychological which will lead to moments in the lives of these peculiar adolescents which will gradually allow teaching the young woman to be a mother or alternatively the rejection of pregnancy and motherhood In the first case which corresponds to most of the situations that were studied the maternity project would end up being assumed albeit through different trajectories